2022
DOI: 10.21315/mjps2022.20.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Intervention Study on Pharmacists’ Knowledge and Counselling on Ophthalmic Preparations in a Tertiary Hospital in South-Western Nigeria

Abstract: The study aimed to assess hospital pharmacists’ knowledge and counselling on ophthalmic preparations before and after an educational intervention was carried out. A cross-sectional study was carried out among 83 pharmacists working at the University College Hospital, Ibadan, Nigeria. A 30-item semi-structured questionnaire was administered to participants to assess their background knowledge and counselling points on use of ophthalmic preparations. An educational intervention was carried out among the pharmaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…The current study observed an improvement in the pharmacists' knowledge and counselling on BP measurement sequel to the educational intervention. Previous intervention studies on medication reconciliation [28], ophthalmic preparations [29], and inhaled asthma medication devices [30] carried out in the same study population all reported similar results, postintervention. This underscores the need for continuous education for hospital pharmacists, especially on patient-focused clinical care activities to improve the quality of service delivered.…”
Section: Discussionsupporting
confidence: 55%
“…The current study observed an improvement in the pharmacists' knowledge and counselling on BP measurement sequel to the educational intervention. Previous intervention studies on medication reconciliation [28], ophthalmic preparations [29], and inhaled asthma medication devices [30] carried out in the same study population all reported similar results, postintervention. This underscores the need for continuous education for hospital pharmacists, especially on patient-focused clinical care activities to improve the quality of service delivered.…”
Section: Discussionsupporting
confidence: 55%